Beyond globalization : making new worlds in media, art, and social practices - Aneesh, A. (Aneesh), 1964-; Hall, Lane, 1955-; Petro, Patrice, 1957- (New directions in international studies., 2012)
Beyond Globalization highlights how mediated practices have become integral to global culture; how social practices have emerged out of computer-related industries; how contemporary apocalyptic narratives reflect the anxieties of a U.S. culture facing global challenges; and how design, play, and technology help us understand the histories and ideals behind the digital architectures that mediate our everyday actions. This provocative volume brings together the best new work of scholars within such diverse fields as history, sociology, anthropology, film, media studies, and art.